2023
DOI: 10.3389/frtra.2023.1152068
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of human amniotic membrane for transplantation in different application areas

Abstract: The human amniotic membrane (hAM) is the inner layer of the placenta and plays protective and nutritional roles for the fetus during pregnancy. It contains multiple growth factors and proteins that mediate unique regenerative properties and enhance wound healing in tissue regeneration. Due to these characteristics hAM has been successfully utilized in ophthalmology for many decades. This material has also found application in a variety of additional therapeutic areas. Particularly noteworthy are the extraordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 245 publications
0
5
0
Order By: Relevance
“…However, it is also critical to understand the impact of processing techniques on the biomolecules embedded within the allografts. 20 A multiplex ELISA detected the proteins contained within LHACM and identified a variety of growth factors and cytokines that regulate vital processes in wound healing including cell migration, proliferation, inflammation, angiogenesis and ECM remodeling. 38 Similar factors have previously been identified in DHACM, a dehydrated amniotic membrane allograft.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also critical to understand the impact of processing techniques on the biomolecules embedded within the allografts. 20 A multiplex ELISA detected the proteins contained within LHACM and identified a variety of growth factors and cytokines that regulate vital processes in wound healing including cell migration, proliferation, inflammation, angiogenesis and ECM remodeling. 38 Similar factors have previously been identified in DHACM, a dehydrated amniotic membrane allograft.…”
Section: Discussionmentioning
confidence: 99%
“…In order to provide the most beneficial and safe amniotic membrane allograft for therapeutic purposes it is necessary to utilize the best methods for collection, processing and storage while preserving the native structure of the amniotic tissue. 20 Extensive analysis of PURION ® processed amniotic membrane allografts has demonstrated that this processing method retains well-known regulatory proteins and preserves the bioactivity to stimulate cellular activities supportive of wound healing. Indeed, increases in proliferation and migration of multiple cell types including stem cells, HDFs, tenocytes, and endothelial cells highlights the ability of amniotic membrane allografts to impact basic cellular functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, dehydrated amnion/chorion membranes (dHACMs) are the most widely utilised for the promotion of wound healing. However, the specific structure and composition of dHACMs, including the presence of amnion or chorion only, or both, along with various matrix components, growth factors and cytokines, depend on the processing methods employed 16–22 . Generally, the amnion and chorion from donated human placentas are isolated through a cleansing proprietary process and either processed separately or laminated to form a two‐layer graft, before being dehydrated under controlled drying conditions 23 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the specific structure and composition of dHACMs, including the presence of amnion or chorion only, or both, along with various matrix components, growth factors and cytokines, depend on the processing methods employed. [16][17][18][19][20][21][22] Generally, the amnion and chorion from donated human placentas are isolated through a cleansing proprietary process and either processed separately or laminated to form a two-layer graft, before being dehydrated under controlled drying conditions. 23 All of the dHACMs that have been utilised in clinical trials to date lack the spongy layer, which bridges the amnion and chorion sides and, thus, is also referred to as an intermediate layer.…”
Section: Introductionmentioning
confidence: 99%